Characterization and prognosis of patients with hepatocellular carcinoma (HCC) in the non-cirrhotic liver - Schütte, Kerstin (BioMed Central, 2014)
BACKGROUND: HCC predominantly develops in the condition of chronic inflammation that has led to liver cirrhosis. A small proportion of patients with HCC is diagnosed in the non-cirrhotic liver (NCL). Data on patients with HCC in NCL in advanced stages are scarce. METHODS: A retrospective analysis was performed comparing 93 patients with HCC in NCL to 571 patients with HCC in liver cirrhosis (LC) with respect to clinical and demographic characteristics. Also factors influencing survival in patients with HCC in NCL were analyzed. RESULTS: Patients with HCC in NCL were diagnosed at older age and in more advanced tumor stages than patients with LC. More than 25% of patients with HCC in NCL presented with extrahepatic metastases. Only a minority of patients with HCC in NCL lacked any sign of hepatic damage. Risk factors for LC and risk factors for NAFLD are present in the majority of patients with HCC in NCL. The BCLC classification corresponded with the survival of patients with HCC in NCL although the therapeutic options differ from those for patients with liver cirrhosis. CONCLUSIONS: It will be one of the major challenges in the future to awake awareness of carrying a risk of hepatic malignancies in patients with chronic liver diseases apart from liver cirrhosis, especially in NAFLD. Surveillance programs need to be implemented if these are cost-effective.